x(x-2)+2x(x+3)+10=3x(x-1)+31

Simple and best practice solution for x(x-2)+2x(x+3)+10=3x(x-1)+31 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x-2)+2x(x+3)+10=3x(x-1)+31 equation:


Simplifying
x(x + -2) + 2x(x + 3) + 10 = 3x(x + -1) + 31

Reorder the terms:
x(-2 + x) + 2x(x + 3) + 10 = 3x(x + -1) + 31
(-2 * x + x * x) + 2x(x + 3) + 10 = 3x(x + -1) + 31
(-2x + x2) + 2x(x + 3) + 10 = 3x(x + -1) + 31

Reorder the terms:
-2x + x2 + 2x(3 + x) + 10 = 3x(x + -1) + 31
-2x + x2 + (3 * 2x + x * 2x) + 10 = 3x(x + -1) + 31
-2x + x2 + (6x + 2x2) + 10 = 3x(x + -1) + 31

Reorder the terms:
10 + -2x + 6x + x2 + 2x2 = 3x(x + -1) + 31

Combine like terms: -2x + 6x = 4x
10 + 4x + x2 + 2x2 = 3x(x + -1) + 31

Combine like terms: x2 + 2x2 = 3x2
10 + 4x + 3x2 = 3x(x + -1) + 31

Reorder the terms:
10 + 4x + 3x2 = 3x(-1 + x) + 31
10 + 4x + 3x2 = (-1 * 3x + x * 3x) + 31
10 + 4x + 3x2 = (-3x + 3x2) + 31

Reorder the terms:
10 + 4x + 3x2 = 31 + -3x + 3x2

Add '-3x2' to each side of the equation.
10 + 4x + 3x2 + -3x2 = 31 + -3x + 3x2 + -3x2

Combine like terms: 3x2 + -3x2 = 0
10 + 4x + 0 = 31 + -3x + 3x2 + -3x2
10 + 4x = 31 + -3x + 3x2 + -3x2

Combine like terms: 3x2 + -3x2 = 0
10 + 4x = 31 + -3x + 0
10 + 4x = 31 + -3x

Solving
10 + 4x = 31 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
10 + 4x + 3x = 31 + -3x + 3x

Combine like terms: 4x + 3x = 7x
10 + 7x = 31 + -3x + 3x

Combine like terms: -3x + 3x = 0
10 + 7x = 31 + 0
10 + 7x = 31

Add '-10' to each side of the equation.
10 + -10 + 7x = 31 + -10

Combine like terms: 10 + -10 = 0
0 + 7x = 31 + -10
7x = 31 + -10

Combine like terms: 31 + -10 = 21
7x = 21

Divide each side by '7'.
x = 3

Simplifying
x = 3

See similar equations:

| 33=41-x | | 5p+6=15 | | f(x-4)=3x^2-5x+4 | | x^2+y=54 | | -4+n=4 | | 3x-4-x=2x+6 | | b-10=-29 | | ax-7n=v | | 4x-2x+6=3x+8-7 | | 10+a=-8 | | 8(n-8)=-152 | | 2(x-7)=x+4 | | -6(x-3)=-72 | | v-4/3(3.14)(21)^ | | 3(2x+4)=2(x-12) | | 16b=160 | | (y^2-2xy)dx+(3x^2-xy^2)dy=0 | | 20+13y=410 | | x/19=15/19 | | v=4.19(21) | | 3x^7+18=-15 | | 116=5w+16 | | 4x-2+6=3x+8-17 | | 3-6x+8x=19 | | 4x-2x+6=3x+8-17 | | 44+y=82 | | 10/22=y/33 | | 44+y=262 | | 1/22=y/33 | | s*7+39=186 | | 1-/22=y/33 | | -3x-4=6x-8 |

Equations solver categories